Visual analysis of the research trend and status on the association between vitamin D and immunity: From 2012 to 2021 - Luo, Xuemei; Deng, Yali; He, Wenfang (Frontiers in Nutrition, 2022)
Objective: We conducted this study to visualize hot spots and trends in the correlation between vitamin D and immunity over the past decade with bibliometric analysis. Methods: We collected relevant articles in the Web of Science Core Collection from 2012 to 2021 as the data source, and then used CiteSpace software to perform the data analysis. Some graphics were done with Graphpad software. Results: A total of 1656 articles were retrieved, with an average citation count of 25.2 times. The USA (439 articles, 26.51%) has the top number of published articles, followed by China (164 articles, 9.90%), England (135 articles, 8.15%), Italy (114 articles, 6.88%), and India (82 articles, 4.95%). The most literature is found in areas of Immunology (337 articles, 20.35%) and Biochemistry Molecular Biology (179 articles, 10.81%). In terms of institutions, the top five institutions with the highest number of publications all belong to Europe. Among them, the League of European Research Universities (LERU) (121, 7.31%) has a greater proportion of output articles. The United States Department of Health Human Services (225, 13.59%) and National Institutes of Health USA (223, 13.47%) funded most articles. The leading five authors with the largest number of publications were Hewison M (19, 1.15%), Bergman P (14, 0.85%), Agerberth B (13, 0.76%), Carlberg C (12, 0.73%), and White JH (12, 0.73%). The top five keywords with the highest co-occurrence frequency are“vitamin d” (367), “d deficiency” (217), “expression” (195), “association” (151), and “d receptor” (132). Among the 17 keyword clusters, the largest cluster is #0 “diet”. Despite cluster #13 “covid-19”, most of the clusters were conducted the studies before 2012. Conclusion: The overall development of research in this field is promising. Western developed countries made outstanding contributions in this area and still take the leading role. But the participation of developing and low-income countries is also impressive. The potential therapeutic effects of vitamin D in immune-related diseases have been noted, especially in multiple sclerosis, COVID-19, etc. This is also the focus and frontier of current research. However, there is still no consensus conclusion in this field. Further research is needed in the future.